Regional Variation in Water-Related Impacts of Shale Gas Development and Implications for Emerging International Plays - Mauter, Meagan (2014)
The unconventional fossil fuel industry is expected to expand dramatically in coming decades as conventional reserves wane. Minimizing the environmental impacts of this energy transition requires a contextualized understanding of the unique regional issues that shale gas development poses. This manuscript highlights the variation in regional water issues associated with shale gas development in the U.S. and the approaches of various states in mitigating these impacts. The manuscript also explores opportunities for emerging international shale plays to leverage the diverse experiences of U.S. states in formulating development strategies that minimize water-related impacts within their environmental, cultural, and political ecosystem.